MODELING OF CLOSE-ORDER FRACTAL STRUCTURES OF METAL-METALLOID ALLOYS WITH CUBIC STRUCTURE - Sereda, D.B.; Baskevуch O.S.; Sereda, B.P.; Kryhliyak, I.V. (Eurasian Physical Technical Journal, 2025)
Using methods of mathematical physics, a comprehensive simulation of the short-range order in Fe₈₈P₁₂ and Cr₈₈C₁₂ alloys produced by electrodeposition was carried out. As the initial configuration for modeling, the crystal structure of the base metal was selected. Numerous experimental studies, including X-ray diffraction and electron microscopy analyses, have indicated that in metal-metalloid alloys, surface microstructures predominantly exhibit ellipsoidal morphologies. Based on these experimental observations, it was hypothesized that the macroscopic ellipsoidal formations observed on the alloy surfaces are composed of clusters with relatively simple geometric configurations, such as spheres or ellipsoids. The results of the simulation revealed that these clusters possess characteristic sizes not exceeding 30-50 angstroms, and their vectorial growth predominantly occurs along a single radial direction relative to the substrate surface. This anisotropic growth behavior is attributed to differences in local atomic bonding energy and diffusion kinetics, which drive the preferential alignment of cluster development. Moreover, it was established that the spatial distribution and size uniformity of the clusters significantly influence the overall mechanical and physicochemical properties of the coatings, including hardness, wear resistance, and corrosion stability. The combination of modeling outcomes with empirical data provides valuable insight into the microstructural evolution mechanisms governing electrodeposited metal-metalloid systems. These findings can serve as a basis for optimizing the electrodeposition parameters to tailor the surface structure and enhance the performance characteristics of functional coatings.